Thus Do the Great: A Critique on Sharh-e- Showq - Mohmmad Yousef Nayyeri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present paper aims to criticizeGhazaliyat - e- Hafez which appears in 5 volumes and 4397 pages. .In this study, the structural and content- based advantages and shortcomings are discussed which are presented as The rise of wisdom, linguistic Horizons, entrance into speech similarities and fashioning of culture.The content-based shortcomings are then analyzed from two points of view: contextual and textual. Moreover, an independent chapter is devoted to the agreement of the book and the principles and presuppositions of the primary source and those of Islam.The last section of the paper draws conclusions from the discussed issues entailing the final judgment about the book. Sharh-e-Showq is accordingly evaluated as among the most valuable and even among the best of the contemporary body of research in the realm of Hafez studies.It can be asserted that it is one of the richest books in terms of investigation and proficiency. It can also be grouped among the best works in the field within the last hundred years. As such, it can play an effective role in furthering the cultural cause in Iran, both strategically and practically.